The Use of Virtual Reality Facilitates Dialectical Behavior Therapy® “Observing Sounds and Visuals” Mindfulness Skills Training Exercises for a Latino Patient with Severe Burns: A Case Study - Gomez, Jocelyn; Hoffman, Hunter G.; Bistricky, Steven L.; Gonzalez, Miriam; Rosenberg, Laura; Sampaio, Mariana; Garcia-Palacios, Azucena; Navarro-Haro, Maria V.; Alhalabi, Wadee; Rosenberg, Marta; Meyer, Walter J.; Linehan, Marsha M. (Frontiers in Psychology, 2017)
Sustaining a burn injury increases an individual's risk of developing psychological problems such as generalized anxiety, negative emotions, depression, acute stress disorder, or post-traumatic stress disorder. Despite the growing use of Dialectical Behavioral Therapy® (DBT®) by clinical psychologists, to date, there are no published studies using standard DBT® or DBT® skills learning for severe burn patients. The current study explored the feasibility and clinical potential of using Immersive Virtual Reality (VR) enhanced DBT® mindfulness skills training to reduce negative emotions and increase positive emotions of a patient with severe burn injuries. The participant was a hospitalized (in house) 21-year-old Spanish speaking Latino male patient being treated for a large (> 35% TBSA) severe flame burn injury. Methods: The patient looked into a pair of Oculus Rift DK2 virtual reality goggles to perceive the computer-generated virtual reality illusion of floating down a river, with rocks, boulders, trees, mountains and clouds, while listening to DBT® mindfulness training audios during 4 VR sessions over a one month period. Study measures were administered before and after each VR session. Results: As predicted, the patient reported increased positive emotions and decreased negative emotions. The patient also accepted the VR mindfulness treatment technique. He reported the sessions helped him become more comfortable with his emotions and he wanted to keep using mindfulness after returning home. Conclusions: Dialectical Behavioral Therapy is an empirically validated treatment approach that has proved effective with non-burn patient populations for treating many of the psychological problems experienced by severe burn patients. The current case study explored for the first time, the use of immersive virtual reality enhanced DBT® mindfulness skills training with a burn patient. The patient reported reductions in negative emotions and increases in positive emotions, after VR DBT® mindfulness skills training. Immersive Virtual Reality is becoming widely available to mainstream consumers, and thus has the potential to make this treatment available to a much wider number of patient populations, including severe burn patients. Additional development, and controlled studies are needed.